Utilization and Management of Bioresources Proceedings of 6th IconSWM 2016 (Springer Singapore, 2018)
The book contains high-quality research papers presented at Sixth International Conference on Solid Waste Management held at Jadavpur University, Kolkata India during November 23-26, 2016. The Conference, IconSWM 2016, is organized by Centre for Quality Management System, Jadavpur University in association with premier institutes and societies of India. The researchers from more than 30 countries presented their work in Solid Waste Management. The book is divided into two volumes and deliberates on various issues related to innovation and implementation in sustainable waste management, segregation, collection, transportation of waste, treatment technology, policy and strategies, energy recovery, life cycle analysis, climate change, research and business opportunities.